Pengembangan E-LKPD Berbasis Somatic Auditory Visualizyion Intellectualy Menggunakan Live worksheet Pada Materi Suhu dan Kalor - ayaa, Wiltia; Rahmi, Aidhia; Anaperta, Megasyani (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2024)
In learning physics, students are less enthusiastic and less active when studying physics. This is because the teaching materials used by students are not in accordance with the students' learning styles and the LKPD used by educators during the learning process does not attract students' interest in learning because it only displays pictures and questions. The aim of this research is to Develop an E-LKPD based on Somatic Auditory Visualization Intellectualy using live worksheets on heat material in class XI SMA that is valid and practical. This type of research is 4D model development research which has four stages, namely: Define, Design, Development and Disseminate. The subjects in this research were 33 educators and students in class XI of the UNP Laboratory Development High School, Padang City. The instruments used in this research were a validity questionnaire and a practicality questionnaire. Then the data that has been obtained is analyzed to see the validity and practicality of the teaching materials. Based on the results of data analysis, it was found that the E-LKPD based on Somatic Auditory Visualization Intellectualy using live worksheets developed was categorized as very valid with an overall average of 86.5%. Apart from that, teaching materials are categorized as very partial with an overall average of 94.16%